Feng Shui as Chinese Cultural Heritage: Influence on Aesthetic Value in Architecture and Interior Design - Fatmawati, Fatmawati; Berlian, Diinaar F.; Alkayis, M. Bukhori (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
This study investigates the influence of Feng Shui, a cornerstone of Chinese cultural heritage, on the aesthetic value of spatial design in architecture and interior design. Feng Shui emphasizes the harmony of energy (qi) within a space and is considered to enhance both comfort and visual appeal. The research utilizes a qualitative methodology with a cross-study approach, including interviews with two professionals in architecture. The findings demonstrate that the application of Feng Shui principles, such as the positioning of the main entrance, natural lighting, air circulation, and the selection of colors and materials, significantly affects both the aesthetics and comfort of a space. As a cultural practice, Feng Shui contributes to visual harmony and functionality and enhances occupants' interaction with their environment. Therefore, it serves as a holistic approach to design, integrating cultural wisdom, aesthetics, functionality, and energy balance to create spaces that are harmonious and comfortable.